(untitled) (Per Musi, 2015)
This article aims at showing that the coordination and control of musical and sports movements emerge essentially from the performer’s action, the task and the surrounding environments. In a dynamic perspective, one concludes that the brain is only one of the many components in this control process, not playing a hierarchically dominant role.